A new history of redemption: the work of Jesus the Messiah through the millennia - McDermott, Gerald R. (Baker Academic, a division of Baker Publishing Group, 2024)
"Taking inspiration from Jonathan Edwards, a widely-respected evangelical theologian traces the redeeming work of the Messiah in the Bible and in church history up through the new heavens and earth"--